Establishment and Phenotypic Analysis of the Novel Gaucher Disease Mouse Model With the Partially Humanized Gba1 Gene and F213I Mutation - Guo, Jia-ni; Guan, Ming; Jiang, Nan; Li, Na; Li, Ya-jun; Zhang, Jin; Ma, Duan (Frontiers in Genetics, 2022)
Gaucher disease (GD) is an autosomal recessive lysosomal storage disorder caused by mutations in the GBA1 gene, which produces the glucocerebrosidase (GCase) protein. There are more than 500 mutations reported in GBA1, among which L444P (p.Leu444Pro) and F213I (p.Phe213Ile) are the most common in the Chinese population, while the function of F213I mutation remains elusive. This study aims to establish the GD mouse model of partially humanized Gba1 gene with F213I mutation. In vitro GCase activity assays showed that the product of partially humanized Gba1 gene, in which the mouse exons 5-7 were replace by the corresponding human exons, displayed similar activity with the wild-type mouse Gba1, while the F213I mutation in the humanized Gba1 led to significant decrease in enzyme activity. ES cell targeting was used to establish the mice expressing the partially humanized Gba1-F213I. Gba1F213I/+ mice did not show obviously abnormal phenotypes, but homozygous Gba1F213I/F213I mice died within 24 h after birth, whose epidermal stratum corneum were abnormal from the wild-type. The GCase activity in Gba1F213I/F213I mice greatly decreased. In conclusion, our results showed that the partially humanized GD mouse model with the F213I mutation was developed and homozygous F213I mutation is lethal for newborn mice.